PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SMK NEGERI 4 CILEGON - Gatot Hartoko; Windi Maylawati (LP2M Universitas Bina Bangsa, 2023)
Human resources are a very important asset that must be improved effectively and efficiently so that optimal performance will be realized. The purpose of this study was to determine the effect of training and work motivation on the performance of Vocational High School (SMK) Negeri 4 Cilegon employees. This study used a quantitative approach using a survey method with a saturated sample whose population was made up of 45 respondents. The results of the study show that training has a significant effect on employee performance, but work motivation has no significant effect on employee performance